Transcriptional Phase Variation at the flhB Gene of Pseudomonas putida DOT-T1E Is Involved in Response to Environmental Changes and Suggests the Participation of the Flagellar Export System in Solvent Tolerance - Segura, Ana (American Society for Microbiology, 2004)
Frameshift mutations in a poly(G) track at the flhB gene of Pseudomonas putida DOT-T1E are responsible for the diminished swimming of this strain on semisolid medium, which contrasts with the high swimming ability of P. putida KT2440, which does not exhibit a poly(G) track at the flhB gene. We previously showed that a mutant lacking FlhB was more sensitive to solvents than the wild-type strain (Segura et al., J. Bacteriol., 183:4127-4133, 2001). In this study, we show that swimming ability correlates with solvent tolerance in P. putida DOT-T1E, so that growth conditions favoring a functional flhB gene (growth on semisolid medium) resulted in increased innate tolerance to a sudden toluene shock.